The Impact of Digital Marketing Strategies on Consumer Behavior in Nepal - Karna, Poonam Kumari Labh (International Journal of Education, Management, and Technology, 2025)
Nepal, digital marketing has had a significant impact on consumer behaviour and changed how companies communicate with their clientele. The impact of important digital marketing techniques on Nepalese consumers' purchase decisions is examined in this study. These tactics include influencer marketing, content marketing, social media marketing, search engine optimisation (SEO), and personalised advertising. The study used a mixed-method technique to gather data from Nepali firms and customers through surveys and interviews. The results show that the best ways to raise brand recognition and encourage purchase intent are through influencer endorsements and social media marketing. The study also outlines obstacles that prevent digital marketing in Nepal from reaching its full potential, including gaps in digital literacy, trust issues, and internet accessibility problems. In order to improve consumer engagement and overcome these obstacles for more successful market penetration, the report ends with actionable suggestions for companies looking to improve their digital marketing strategy.